Pelatihan Software Perkantoran Bagi Pembina Wanita Katolik Republik Indonesia - Elsje Kosasih; Tanto Kurnia (Universitas Mataram, 2019)
In its 18th Congress in 2008, the Catholic Women’s Association of Indonesia (WKRI), a mass organization, set a program of “increasing small business women” (PPUK) as a program to help lift women to be able to run businesses in the economic sector. Therefore, WKRI has to empower the supervisors of this PPUK to be able to assist their fostered group and to give management guidance for the participants’ businesses. Current business management can be done more easily if business actors can use various office software that is easily obtained at the moment. This software is intended to make business letters, simple financial reports, attractive presentations, even flyers or other promotional media easier. The supervisors who will assist their fostered groups, will be equipped with the expertise of various office software, to later teach those who manage businesses. An interesting phenomenon that could be observed is that the supervisors involved in this PPUK program are generally more than 40-50 years old, even some of them are more than 60 years old. Making modules that are easy to understand and easy to teach to participants is a must. This training was carried out in 10 meetings from May to July 2019 and was attended by more than 20 supervisors of WKRI West Java Regional Leadership Council and Bandung Branch. It gained good feedback from the participants